2023
DOI: 10.1123/jsr.2021-0443
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Rink Hockey-Related Injuries

Abstract: Context: Determining the rate of injuries related to a certain sport is accepted as the primary step toward designing, implementing, and evaluating injury prevention programs. The aim of this study was to examine the injuries sustained by semiprofessional Spanish rink hockey players and to compare data per playing position. Design: Observational and retrospective. Methods: Athletes from 21 teams were surveyed via a self-reported questionnaire to screen for incidence, injury burden, location, tissue, and onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…The muscle and tendinous injuries were the most frequent in this localization, with the thigh adductor muscles being the most frequently affected. These data confirm those of previous studies [9,13,30] that the adductor muscles are most frequently affected in skating sports. These can be explained by the role of adductor muscles in the stabilization of hip and pelvis during hip flexion in lateral sliding, with a flexion and internal rotation of the thigh [31] On the other hand, the latter present a lower incidence of hamstring injuries than in other sports such as soccer or field hockey.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The muscle and tendinous injuries were the most frequent in this localization, with the thigh adductor muscles being the most frequently affected. These data confirm those of previous studies [9,13,30] that the adductor muscles are most frequently affected in skating sports. These can be explained by the role of adductor muscles in the stabilization of hip and pelvis during hip flexion in lateral sliding, with a flexion and internal rotation of the thigh [31] On the other hand, the latter present a lower incidence of hamstring injuries than in other sports such as soccer or field hockey.…”
Section: Discussionsupporting
confidence: 92%
“…The most frequent localization of injuries was in the lower limb, more specifically, the groin/thigh area. The same tendency has been reported in other studies on RH 11 13 and other skating sports 28 29 . The muscle and tendinous injuries were the most frequent in this localization, with the thigh adductor muscles being the most frequently affected.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…High prevalence of seasonal groin problems has been historically associated to football or ice hockey, due to their multidirectional nature [1,22]. Recent investigations have shown that groin pain is similar in elite and amateur rink hockey athletes [7,23].…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence of seasonal groin problems has been historically associated with football/soccer or ice hockey, due to their multidirectional nature 1 22 . Recent investigations have shown that groin pain is similar in elite and amateur rink hockey athletes 7 23 . Fifty-three percent of adult male ice hockey and football players suffer groin problems annually 11 12 , which is almost identical to the 50% observed in this cohort of senior players (both genders).…”
Section: Discussionmentioning
confidence: 99%